Food-drug interactions: genotoxicological aspects - A. D. Durnev (Фармакокинетика и Фармакодинамика)
Resume. Reviewed phenomenology of food-drug interactions, pharmacokinetic and other targets of this interaction. The attention is focused on possible genotoxic adverse events by food-drug interactions.